DOCKING MOLEKULER SENYAWA METABOLIT SEKUNDER Lantana camara SEBAGAI ANTIINFLAMASI TERHADAP ENZIM COX-1 - Dian Puspitasari; Eili Supriatin S.W; Khoirul Ummah; Dinik Rokhmatin; M. Musthofa Mubarrok; Ajheng Triyuni Hariza; Isnawati Isnawati; Erlix Rakhmad Purnama; Atim Febry Masula (Biota, 2018)
Lantana camara contains several types of flavonoids such as Umuhengerin, Lantadene A, Lantadene B, Icterogenin.One of the mechanisms of action of flavonoids as antiinflammatoryis by inhibiting cyclooxygenase receptor (COX). This study aims to determine the affinity of flavonoid compounds contained in L. camara with COX-1 receptors as antiinflammatory and to know the hydrogen bonds that can be formed by using molecular docking method. Testing in silico is done based on computer-aided drug design method. The tools used in this study, the PyRx software, PyMol software, Pubchem (database compound), PDB (Protein Data Bank), and PoseView. Based on the results of the docking and discussion above it can be concluded that the Icterogenin compound and Umuhengerin compound is the most effective compound in antiinflamasi process, Icterogenin compound has a value RMSD 41.1 Å and the value of binding afinity -8.8 and the Umuhengerin compound has value RMSD 1, 61 Å and value of binding affinity -8.0. It shows that the Umuhengerin compound has a resemblance percentage with the target protein because it has a smaller RMSD value than the Icterogenin compound. However, Icterogenin compounds have stronger and more efficient hydrogen bonds than the Umuhengerin compound because of the lowest value of binding affinity.